2013
DOI: 10.3897/zookeys.266.3982
|View full text |Cite
|
Sign up to set email alerts
|

The amphibians and reptiles of Luzon Island, Philippines, VIII: the herpetofauna of Cagayan and Isabela Provinces, northern Sierra Madre Mountain Range

Abstract: We provide the first report on the herpetological biodiversity (amphibians and reptiles) of the northern Sierra Madre Mountain Range (Cagayan and Isabela provinces), northeast Luzon Island, Philippines. New data from extensive previously unpublished surveys in the Municipalities of Gonzaga, Gattaran, Lasam, Santa Ana, and Baggao (Cagayan Province), as well as fieldwork in the Municipalities of Cabagan, San Mariano, and Palanan (Isabela Province), combined with all available historical museum records, suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 104 publications
(287 reference statements)
1
18
0
Order By: Relevance
“…Important habitats we observed that are critical to species survival include riparian vegetation, leaf litter, tree stumps, dead logs, fallen trees, tree foliage, swamps, and creeks, all of which are found in forested areas. Our observations are consistent with those from other studies Brown et al 2001Brown et al , 2012Brown et al , 2013bMcleod et al 2011;Siler et al 2011Siler et al , 2012Gaulke 2011;Devan-Song & Brown 2012;Plaza & Sanguila 2015;Siler et al 2016), emphasizing how these habitats are among the highest priority for research and conservation value.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Important habitats we observed that are critical to species survival include riparian vegetation, leaf litter, tree stumps, dead logs, fallen trees, tree foliage, swamps, and creeks, all of which are found in forested areas. Our observations are consistent with those from other studies Brown et al 2001Brown et al , 2012Brown et al , 2013bMcleod et al 2011;Siler et al 2011Siler et al , 2012Gaulke 2011;Devan-Song & Brown 2012;Plaza & Sanguila 2015;Siler et al 2016), emphasizing how these habitats are among the highest priority for research and conservation value.…”
Section: Discussionsupporting
confidence: 83%
“…Repeated surveys in different seasons or times per year, focusing on variety of habitats, and systematic analysis of natural populations are necessary to determine if the species populations are increasing or declining. If these data are not available, assessment of species conservation status will be of limited value, incomplete, or much worse, providing incorrect information, which can mislead conservation planning (e.g., the case of Platymantis polillensis in the Philippines; Brown et al 2012Brown et al , 2013b.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations